Writing the natural way using right-brain techniques to release your expressive powers - Rico, Gabriele L. (New York Tarcher, 2000)
Writing the Natural Way, first published fifteen years ago, has shown hundreds of thousands of readers how to turn the task of writing into the joy of writing. Completely revised, newly illustrated, and with a wealth of updated, field-tested exercises, this popular classic will help unlock natural writing styles and storytelling abilities.
Includes bibliographical references (p. 249-256) and index.
Keywords: English language--Rhetoric.